Beliefs and attitudes regarding prenatal marijuana use: Perspectives of pregnant women who report use. (1st March 2019) - Chang, Judy C.; Tarr, Jill A.; Holland, Cynthia L.; De Genna, Natacha M.; Richardson, Gale A.; Rodriguez, Keri L.; Sheeder, Jeanelle; Kraemer, Kevin L.; Day, Nancy L.; Rubio, Doris; Jarlenski, Marian; Arnold, Robert M.
Highlights: Pregnant women who use marijuana have complicated feelings about marijuana. Pregnant women who use marijuana believe it to be safer than other substances. Women were worried about marijuana's uncertain risks to their pregnancy and child. There were mixed beliefs regarding whether marijuana was addictive. Women noted prenatal marijuana use risked involvement of child protective services. Abstract: Objective: With the increasingly permissive legal and social environments regarding marijuana, it is important to understand prenatal marijuana use from the perspective of women who use marijuana. Our objective was to qualitatively describe the marijuana use experiences, beliefs, and attitudes of women who used marijuana during pregnancy. Methods: We conducted semi-structured interviews with pregnant women who had either reported current marijuana use or had urine testing positive for marijuana. Interviews were transcribed verbatim and analyzed for patterns and themes. Results: Twenty-five pregnant women who used marijuana during their pregnancies participated in our study interviews. Main themes that emerged from the interviews were that women: 1) reported higher amounts of marijuana use prior to pregnancy and attempted to reduce their use once they realized they were pregnant; 2) used marijuana to help with nausea and appetite changes during pregnancy or to improve mood; 3) described marijuana as "natural" and "safe" compared to other substances such as alcohol, tobacco, other recreational drugs, and prescribed medications; 4) had conflicting opinions regarding whether marijuana was addictive; and 5) were uncertain but had some concerns regarding potential risks of prenatal marijuana use. Conclusion: Pregnant women who used marijuana in pregnancy held contradictory beliefs about continued use; they reported trying to reduce usage and were worried about potential risks, but also felt that marijuana is more natural and safer than other substances, including prescribed medicines. These findings have implications for how practitioners address prenatal marijuana use and highlight the need for further research on developmental outcomes.